2007
DOI: 10.1111/j.1472-4669.2007.00100.x
|View full text |Cite
|
Sign up to set email alerts
|

The control of organic matter on microbially mediated iron reduction and arsenic release in shallow alluvial aquifers, Cambodia

Abstract: Microbes may play a key role in the mobilization of arsenic present in elevated concentrations within the aquifers extensively exploited for irrigation and drinking water in West Bengal, Bangladesh, and in other regions of South‐East Asia. Microcosm experiments using Cambodian sediments (which are also representative of other similar reducing aquifers containing arsenic‐rich waters) show that arsenic release and iron reduction are microbially mediated and demonstrate that the type of organic matter present, no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
135
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(153 citation statements)
references
References 69 publications
17
135
0
Order By: Relevance
“…Reducing conditions with low redox potentials can facilitate As release in groundwater (Bhattacharya et al, 1997;McArthur et al, 2001;Rowland et al, 2007;Mladenov et al, 2010). The elevated As concentrations in the groundwater of the Datong and Hetao Basins were influenced very strongly by ORP values (Fig.…”
Section: Impact Of Redox Potential On Groundwater As Occurrencementioning
confidence: 99%
“…Reducing conditions with low redox potentials can facilitate As release in groundwater (Bhattacharya et al, 1997;McArthur et al, 2001;Rowland et al, 2007;Mladenov et al, 2010). The elevated As concentrations in the groundwater of the Datong and Hetao Basins were influenced very strongly by ORP values (Fig.…”
Section: Impact Of Redox Potential On Groundwater As Occurrencementioning
confidence: 99%
“…This topographic index, combines local upslope contributing area and slope and seems to be a key to understand much of the hydrological processes and soil properties (Sørensen et al, 2006;Yimer et al, 2006). It is reported that TWI was positively correlated with soil organic matter (Pei et al, 2010), which indirectly supports the central role of organic matter in the mobilization of As in groundwater Fendorf et al, 2010;Rowland et al, 2007). As expected from Fig.…”
Section: Logistic Regression Modelmentioning
confidence: 54%
“…with less than 1 % organic matter (OM) [33][34][35] and they contain different types of OM. Recent studies in sediments from arsenic hot spots in West Bengal, [27,36] Cambodia, [22,37] and Taiwan [38] have shown that extractable OM, including long chain n-alkanes and other hydrocarbons of immature (e.g. petroleum) origin are present.…”
Section: Introductionmentioning
confidence: 99%
“…[20,24] As V reduction was shown repeatedly in a series of microcosm studies set up with sediments from arsenic affected aquifers, where simple organic proxies such as acetate or lactate were used to stimulate microbial mobilisation of arsenic. [15,19,20,22,25,26] Molecular studies in some of these systems revealed the presence of known Fe III and As V respiring bacteria, as well as arsenate respiratory reductase gene sequences. [19,[25][26][27] Nevertheless, the identification of the active members of the microbial communities in these complex sedimentary environments is challenging, especially when investigating specific microbe-substrate interactions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation